Secondary School Students’ Attitudes Towards National Values and Political Participation in Zamfara State, Nigeria - Mansur Ibrahim; Sule Muhammad (Penerbit Hellow Pustaka, 2026)
This study examined the influence of the Civic Education curriculum on secondary school students’ attitudes toward national values and their political participation in Zamfara State, Nigeria. The study was guided by three objectives, three research questions, and three null hypotheses. A descriptive survey research design was adopted. The population comprised secondary school students, while a sample of 384 respondents was selected using a multistage sampling technique. Data were collected using a structured questionnaire validated by experts and tested for reliability, yielding a Cronbach alpha coefficient of 0.91, which indicates high internal consistency. Data were analyzed using descriptive statistics and regression analysis at 0.05 level of significance. Findings revealed that the Civic Education curriculum has a significant positive influence on students’ attitudes toward national values and their level of political participation. The results further showed that Civic Education teaching methods significantly affect both students’ civic attitudes and their engagement in political activities. The study also established that interactive and student-centered teaching approaches strengthen the effectiveness of the curriculum in shaping civic awareness and democratic participation among students. The study concludes that Civic Education plays a vital role in promoting responsible citizenship and democratic values among secondary school students in Zamfara State, although its effectiveness largely depends on the quality of instructional methods used in delivery.